Dipeptidyl peptidase‐4 inhibitor‐related bullous pemphigoid: A comparative study of 100 patients with bullous pemphigoid and diabetes mellitus. Issue 4 (4th February 2021) - Chanprapaph, Kumutnart; Pratumchart, Nathathai; Limtong, Preeyachat; Rutnin, Suthinee; Sukasem, Chonlaphat; Kungvalpivat, Pintusorn; Triamchaisri, Siripich; Suchonwanit, Poonkiat
Abstract: Dipeptidyl peptidase‐4 inhibitor (DPP4i)‐associated bullous pemphigoid (BP) has been emerging but whether it has genotype or phenotype differences from idiopathic BP (IBP) remains to be determined. We aimed to compare clinical characteristics, genetic susceptibility, laboratory features, disease activity, and outcomes between DPP4i‐associated BP (DBP) and IBP occurring among patients with diabetes mellitus type 2 (T2DM). Medical records of patients diagnosed with BP and T2DM from January 2009 to December 2019 were retrospectively reviewed, and patients were categorized into DBP or IBP groups. Of 100 patients, 23 had DBP and 77 had IBP. There was no difference in the Bullous Pemphigoid Disease Activity Index score between the two groups; however, the score for urticaria and erythema was less in DBP ( p  < 0.001), indicating a non‐inflammatory phenotype. The HLA‐DQB1*03:01 allele was more commonly present in the DBP than IBP cases (odds ratio = 5.33 [95% confidence interval, 1.11–28.59], p  = 0.016). The absolute eosinophil count was significantly lower in the DBP group ( p  = 0.002). Likewise, eosinophilic spongiosis was found less frequently in DBP cases ( p  = 0.005). Patients in the DBP group had a significantly higher percentage of complete remission on therapy compared to the IBP counterpart ( p  = 0.026) after DPP4i discontinuation. Moreover, the mean maximum dosage of prednisolone administrated per patient was significantly lower in drug‐related cases ( p  = 0.012). In conclusion, our cohort in Thai patients with T2DM confirms the differences between phenotype and genotype characteristics of DBP and IBP. We emphasize the importance of drug discontinuation in all DPP4i‐related cases because doing so may lead to a better disease outcome.